Three roads to the welfare state : liberalism, social democracy and Christian democracy - Fanning, Bryan (Bristol : Policy Press, 2021)
Bryan Fanning traces the development of European welfare states in this accessible analysis of social change from the Industrial Revolution onwards. The book explores evolutions through the lens of three traditions - social democracy, Christian democracy and liberalism - with insights into the people and beliefs that influenced each.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Welfare state -- Europe; Europe -- Social policy; Christian democracy -- Europe